A closed modified V-shaped uniplanar triple band ACS fed antenna for wireless applications - Anuj Kumar; Anukul Jindal; Apurva Singh; Reshma Roy; Om Prakash Kumar; Tanweer Ali (Institute of Advanced Engineering and Science, 2020)
In the proposed paper, a uniplanar asymmetric coplanar strip (ACS) fed antenna with closed V-shaped radiating patch of size printed on FR4 substrate with loss tangent ( =0.02, height (h)=1.6mm, and dielectric constant of 4.4 covering WiMAX, X-band and WLAN applications is presented. The closed V-shaped radiating patch is formed by joning two rectangular stubs. The remaining radiating part is obtained by adding rectangular strips to feed to obtained multiband operation. The advantage of this structure is that it forms simple configuration as well as helps the antenna attaining three distinict useful frequency band with good impedance matching for S11 less than -10 dB criteria. The proposed antenna operates at 3.1 (WiMAX), 5.0 (WLAN) and 9.9 (X-band) GHz in simulation. Under measurement the proposed antenna shows multiband phenomenon at 3.2, 5.3 and 9.7 GHz, respectively. The antenna exhibits simulated gain of 2.51, 1.18 and 1.96 dB at 3.1, 5.0 and 9.9 GHz. The key parameters of the antenna like length and width of the multi-branched strips are optimized to get the multiband operation. The evolution and optimization process is dealt in detail with the help of S11, VSWR, current distributions, radiation patterns and gain.